Kingdom of the Netherlands-Netherlands : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the 2004 Article IV Consultation on the Kingdom of the Netherlands-Netherlands highlights the economic developments and policies. The economy is beginning to emerge from an extended downturn. Meanwhile, against a background of soft labor market conditions and economic slack generally, inflation pressures are low. The authorities acknowledged the economic reasoning behind these recommendations, but considered implementation politically difficult in light of a cultural preference for an egalitarian wage distribution.